PTH-061 Improving bowel prep and colonoscopy understanding with an educational video. (June 2019) - Archer, Thomas; Lal, Nikhil; Emms, Claire; Baxter, Andrew; Dear, Keith; Blanco, Adolfo Parra; Thoufeeq, Mo
Abstract : Introduction: Bowel preparation (BP) is key to high quality colonoscopy. Up to 20% of colonoscopies may be limited by inadequate BP. Good quality BP is shown to increase Adenoma Detection Rate, and reduces procedure length. Understanding and adherence to instructions is associated with quality of BP. The use of visual aids can lead to improved BP. We aim to introduce an educational video as a quality improvement project and assess its acceptability and impact on patients' understanding of how to take BP for colonoscopy. Method: A video was created in collaboration with the Nottingham Trent University graphics department. The video was reviewed by a patient involvement group and doctors. Patients referred for colonoscopy were included. An initial survey of patients was conducted to assess their understanding of colonoscopy and BP. Subsequently, a group of patients referred for a colonoscopy watched the educational video and completed questionnaires. Outcome data from their endoscopy reports was also accessed to assess adequacy of BP. Results: A preliminary survey of patients demonstrated that 10/47 patients rated their understanding of a colonoscopy procedure or how to take BP as 5/10 or less on a visual analogue scale (VAS). 38% of these patients had inadequate BP, compared with 8% of the patients whose score >5/10. Subsequently 32 patients (male to female ratio 1:1) were recruited and were shown the educational video. The mean age was 64 and the range was 49–83. 22 patients rated the acceptability and how easy it was to follow the video as 10/10. 3 rated the acceptability and how easy it was to follow the video < 5/10. 24 (75%) patients indicated that the video improved their understanding of what a colonoscopy involved, 1 indicating a decrease in understanding and the remaining 7 patients indicating no change in understanding. 24 of patients who viewed the video had a colonoscopy of whom 1 patient had inadequate BP, 4 had fair BP and 19 had good or excellent BP.1 Conclusion: The majority of patients in this cohort found the video both acceptable and easy to follow and improved understanding of what a colonoscopy involved and how to take BP for the procedure. Although the sample was small and wasn't matched to controls, the outcome in terms of adequacy of BP was excellent. The data indicates that an educational video would be acceptable and could improve both understanding of the procedure and how to take BP. A randomised study comparing patients with access to a video versus no access would confirm the benefit of standard use of this educational tool for patients.